2017
DOI: 10.4103/ijc.ijc_114_17
|View full text |Cite
|
Sign up to set email alerts
|

An audit and analysis of different causes of defaults in patients receiving radiation for head and neck cancers: A tertiary regional cancer center experience

Abstract: Radiation-induced acute toxicity, socioeconomic status and distance plays minimal role as a cause of patients who stop taking EBRT. There is no particular relation between age, disease site, treatment received before radiotherapy, intent of treatment, and concurrent chemoradiation-induced acute reactions with defaults among patients. Loss of income and work in the poor population during the treatment may be an important possible cause of defaults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Around 10% of all patients on radiotherarpy have unplanned/unintended treatment interruption. Literature has reported that around 20% of patients default radiotherapy in real-world setting ( Roick et al, 2018 , Pujari et al, 2017 ). In our institution, this figure is much higher .i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Around 10% of all patients on radiotherarpy have unplanned/unintended treatment interruption. Literature has reported that around 20% of patients default radiotherapy in real-world setting ( Roick et al, 2018 , Pujari et al, 2017 ). In our institution, this figure is much higher .i.e.…”
Section: Discussionmentioning
confidence: 99%